African music in Christian worship - Louw, Johan K. (International Library of African Music, 1958)
In “African Music”, volume 1, No. 3, I wrote, “When one true African Christian musician is brought to disregard any form of church music that he may have known in the past and breaks forth praising God in the musical medium that lies closest to his heart, half the battle will have been won. This is not impossible.” I maintained that very much of what was found in the Nyanja hymnbook I was familiar with was completely foreign to the African Christians who were using the book, and that it was not only not too late to start using African Music through the instrumentality of African musicians, but that it was “essential that a start should be made, and that as soon as possible.” Can it be done? This, after all, is the crux of the matter, and unless it is possible to get down to some practical scheme in which Africans will play their part and African artists themselves satisfy the need, it is little use discussing the matter. I believe it is possible to get down to such a scheme provided the necessary staff and financial assistance for an African Music Centre, could be found. How such a Centre should be run is a matter for further investigation and experimentation. There are, however, some practical suggestions I should like to make, which, I think, can lead to very useful results.
Keywords: Ethnomusicology; Chewa (African people); Nyanja (African people); Music; Christianity; Africa; Education; Church Worship; African Music; Religious Aspects